A bivalent subunit vaccine efficiently produced in Pichia pastoris against SARS-CoV-2 and emerging variants - Xu, Huifang; Wang, Tiantian; Sun, Peng; Hou, Xuchen; Gong, Xin; Zhang, Bin; Wu, Jun; Liu, Bo (Frontiers in Microbiology, 2023)
The emergence of severe acute respiratory syndrome coronavirus type II (SARS-CoV-2) variants have led to a decline in the protection of existing vaccines and antibodies, and there is an urgent need for a broad-spectrum vaccination strategy to reduce the pressure on the prevention and control of the pandemic. In this study, the receptor binding domain (RBD) of the SARS-CoV-2 Beta variant was successfully expressed through a glycoengineered yeast platform. To pursue a more broad-spectrum vaccination strategy, RBD-Beta and RBD-wild type were mixed at the ratio of 1:1 with Al(OH)3 and CpG double adjuvants for the immunization of BALB/c mice. This bivalent vaccine stimulated robust conjugated antibody titers and a broader spectrum of neutralizing antibody titers. These results suggested that a bivalent vaccine of RBD-Beta and RBD-wild type could be a possible broad-spectrum vaccination strategy.